CLONING OF GS1 GENE ENCODES GLUTAMINE SYNTHETASE 1 AND CONSTRUCTION OF TRANSFORMATION VECTOR - Van Thang, Bui; Van Thanh, Ngo; Thi Hong Gam, Nguyen; Hoang Ha, Chu (Journal of Forestry Science and Technology, 2016)
Glutamine synthetase (EC 6.3.1.2) is an enzyme which assimilates ammonium into amino acids. Therefore, GS plays an essential role in the metabolism of nitrogen. In vascular plants, GS is devided into two groups: cytosol - located isoform (GS1) and plastid – located isoform (GS2). Surveys have shown that GS1 gene was used widely to generate transgenic plants. Effects on the growth characteristics of GS1 transgenic plants have been reported in many researches. In this research, in order to prepare for generating GS1 transgenic plants, the 1074 bp – length cDNA of GS1 gene is successfully cloned from Pinus sylvestris. Compared the sequence of the isolated cDNA of GS1 with other sequences on Genbank (Accession number X69822.1 and X74429.1), the similarities are both higher than 99%. This result indicates a high sequence conservation of GS1 gene. The gene was then ligated into vector pBI121 to construct transformation vector pBI121 – GS1 which can be used in next steps to generate transgenic plants which have high - growth rate.